SEMIOTIC ANALYSIS OF HOTEL ADVERTISEMENT - Km Tri Sutrisna Agustia (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2021)
The phenomenon of misinterpretation and the mismatch of the desired meaning in a hotel advertisement gives significant losses to hoteliers in Bali. The purpose of this study is to understand the meaning contained in a hotel promotion advertisement. This study aims to align the problem of conveying meaning in promotional advertisements that are often not understood by tourist targets so that there is a misunderstanding between the wishes of the hotel marketing and the needs of the tourists themselves. This study analyzes (1) ads part segmentation, (2) describes the relationship between signs in the form of markers and signs in hotel advertisements, (3) describes and provides an overview of suggestions regarding the role of the proper meaning in hospitality advertisements. The design of this study uses a qualitative design collected from study subjects in the form of hotel advertisements collected from promotional advertisements (brochures or websites) of hotels in Bali. The objects in this study are in the form of words, phrases, sentences, and images in the advertisements. The study stage begins with data collection on hotel advertisements regarding the advertisements being promoted. Then a picture of the proper meaning of promotional advertising based on semiotics will be drawn up. The results achieved are the connection between symbols and meanings used in a hotel promotion advertisement. Semiotic science variables can be added in the design of a hotel advertisement so that it provides an illustration of the suitability between the application of semiotics and hotel marketing practices as outlined in the advertisement. The exact match between the desires and the meaning to be conveyed can be developed properly to avoid misunderstandings between the hotel and the target market. Keywords: advertising; Bali; hospitality; promotion; semiotics